2012
DOI: 10.1016/j.jmbbm.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The influence of collagen–glycosaminoglycan scaffold relative density and microstructural anisotropy on tenocyte bioactivity and transcriptomic stability

Abstract: Biomaterials for orthopedic tissue engineering must balance mechanical and bioactivity concerns. This work describes the fabrication of a homologous series of anisotropic collagen–GAG (CG) scaffolds with aligned tracks of ellipsoidal pores but increasing relative densities (ρ*/ρs), and we report the role scaffold relative density plays in directing tenocyte bioactivity. Scaffold permeability and mechanical properties, both in tension and compression, were significantly influenced by relative density in a manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 55 publications
1
86
0
Order By: Relevance
“…This variant was chosen for its ability to prevent significant tenocyte-mediated contraction, along with the resultant loss of tenocyte alignment and downregulation of tenocyte-specific gene profiles, during long-term culture. 47 However, as they are three times denser than previous scaffolds, it is critical to examine strategies to improve tenocyte recruitment as well as subsequent proliferation and metabolic activity and compare the effectiveness of diffusion-mediated biomolecule transport versus sequestered biomolecules for enhancing the tenocyte response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This variant was chosen for its ability to prevent significant tenocyte-mediated contraction, along with the resultant loss of tenocyte alignment and downregulation of tenocyte-specific gene profiles, during long-term culture. 47 However, as they are three times denser than previous scaffolds, it is critical to examine strategies to improve tenocyte recruitment as well as subsequent proliferation and metabolic activity and compare the effectiveness of diffusion-mediated biomolecule transport versus sequestered biomolecules for enhancing the tenocyte response.…”
Section: Discussionmentioning
confidence: 99%
“…21 The anisotropic scaffold variant used throughout these studies was previously shown to support a high tenocyte bioactivity, while resisting a tenocyte-mediated contraction. 21,47 Scaffold crosslinking Dry scaffolds were dehydrothermally crosslinked at 105°C for 24 h under vacuum ( < 25 torr) in a vacuum oven (Welch) following lyophilization. Chemical crosslinking of scaffolds was achieved using carbodiimide chemistry with a solution of 1-ethyl-3-[3-dimethylaminopropyl] carbodiimide hydrochloride (EDC; Sigma-Aldrich) and N-hydroxysulfosuccinimide (NHS; Sigma-Aldrich) at a molar ratio of 5:2:1 EDC:NHS:COOH 48,49 for 1 h at 37°C.…”
Section: Cg Suspension Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Advancements in engineering, chemistry and biology have made available numerous technologies that allow fabrication of hierarchical threedimensional scaffolds that closely imitate native tendon architectural features and mechanical properties, whilst enabling localised and sustained delivery of therapeutics [350]. Collagen sponges, for example, with or without aligned tracks and loaded with GAGs, growth factors and various cell populations have demonstrated enhanced cell motility and phenotype maintenance in vitro and increased collagen expression levels in small animal models [351][352][353][354][355]. However, such scaffold conformations cannot provide adequate mechanical resistance, in such a high mechanical demand environment [356].…”
Section: Bottom-up Approached For Tendon Repair Based On Natural In Omentioning
confidence: 99%
“…Also, the absorption rate is fast so that few days after implantation, the architecture is completely depleted by the inflammatory cells and mediators 2,12 . Moreover, the orientation of their polymerized fibres is randomized and is not suitable for the purposes of tendon tissue engineering 2,50,56 . Porous scaffolds are used to produce both bi-and tridimensional scaffolds with different purposes (Fig.…”
Section: Architecture Of the Scaffoldsmentioning
confidence: 99%